Celebrating Adam Watkins' 4th Birthday at Special Spot - Watkins, Howard::::::::: (1982)
Seth Tilley, Devon Bleile-Kratzer, Annie Tilley, Sandy Jones, Adam Watkins, Andy?, Clay Quentin ? , Art Wille Held at Huntington Blvd. home of Jim Kratzer and Nancy Bleile